Animated Cartoons to Develop Listening Skill and Vocabulary - Devi Krishnan, Prisla; Md Yunus, Melor; Md Yunus, Melor; ., . (International Journal of Engineering and Technology, 2018)
English language is a second language to most pupils in Malaysia. The importance of mastering English language to a certain level of proficiency is highlighted in the National Education Blueprint - 2013-2025. Many of the pupils have very strong mother tongue (L1) influence which hinders the acquisition of English language. The lack of exposure to English language has resulted to limited vocabulary among pupils from rural and semi-urban schools. This has led them to being weak in English language. The use of â€œAnimated Cartoonsâ€ via YouTube is introduced to develop their listening skills and expand their vocabulary in order to master English language. Thus, the focus will be on 10 weak ability Form 1 pupils with strong influence of L1 background. Data was collected based on pre and post-test score and a questionnaire survey data was also collected and analysed using descriptive statistic. The findings found that the use of â€˜Animated Cartoonsâ€ had a positive impact on the pupils and increased their acquisition of vocabulary and listening skills. Thus, it is crucial that the use ICT be integrated in English language curriculum to enable low proficient pupilsâ€™ mastery of the language and fulfil the vision in the National Education Blueprint.Â Â